A multi-color stacking synthesis process for colored crystal jade
By using specific proportions of oxide raw materials and step-by-step heating heat treatment technology in the multi-color lamination synthesis process of color crystal jade, the problems of color crystal jade in composition and proportion control are solved, and the effects of high hardness, chemical stability and gloss are achieved, and it is suitable for the construction and decoration fields.
Patent Information
- Application Number
- CN202411139964.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-08-19
AI Technical Summary
During the multi-color lamination and synthesis of colored crystal jade, it is difficult to accurately control the composition and proportion of each layer of materials, resulting in uneven color, poor gloss, insufficient chemical stability and hardness.
A specific ratio of Al2O3, P2O5, BaO, CaO, MgO, and R2O are used as raw materials, and melt and secondary melt crystallize by step-by-step heating and heat treatment to form a dense microcrystalline glass structure.
It improves the chemical stability and hardness of colored jade, ensures the diversity of colors and high gloss, and is suitable for use in the fields of architecture and decoration.
Smart Images

Figure BDA0005000992520000101 
Figure BDA0005000992520000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microcrystalline glass, and in particular relates to a multi-color stacking synthesis process of colored crystal jade. Background Art
[0002] Jade is a polycrystalline aggregate with a complex composition. Multiple mineral components are combined in a specific form to form a unique texture and beauty.
[0003] Colored crystal jade, as the name implies, is a new type of material that combines color with the beauty of jade. The addition of color makes the jade composition more complex. At present, colored crystal jade is mostly prepared by multi-color stacking. However, in the process of multi-color stacking synthesis, the composition and proportion of each layer of materials need to be precisely controlled to ensure that the color and texture of the final product meet expectations. However, due to the complexity of jade composition, problems such as uneven composition, color distortion, and poor surface gloss are prone to occur in this process. Moreover, the combination of different materials needs to solve the problem of structural stability to ensure that the stacked structure will not fall off or deform during long-term use. In addition, colored crystal jade is generally used to prepare artistic buildings or artworks, which need to be preserved for a long time. Therefore, in addition to aesthetics and gloss, how to improve the chemical stability and hardness of colored crystal jade is also a problem to be solved at present. Summary of the invention
[0004] The purpose of the present invention is to provide a multi-color stacking synthesis process of colored crystal jade. The present invention is simple to operate, and the prepared colored crystal jade has rich colors, high surface gloss, high hardness, and certain chemical stability, and is very suitable for application in the fields of construction, decoration, etc.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A multi-color stacking synthesis process of colored crystal jade comprises the following steps:
[0007] S1. Weigh the raw materials according to the required color system, mix and melt them into samples of different colors and shapes;
[0008] S2, stacking samples of different colors and shapes according to the required colors and shapes, and fixing them with a fixative solution to obtain a precursor sample;
[0009] S3, subjecting the precursor sample to secondary melting and crystallization to form a primary sample;
[0010] S4. Process the initial sample to obtain.
[0011] The raw materials, by mass percentage, are: 0.01% to 7% of coloring component and the balance of basic component to 100%.
[0012] Calculated by weight percentage of the raw materials, the coloring components are Fe2O3: 0-1.5%, Mn2O3: 0-5%, Cr2O3: 0-4%, CuO: 0-4%, Cu2O: 0-4%, CoO: 0-2%, Co2O3: 0-5%, NiO: 0-0.5%, Er2O3: 0-0.5%, Bi2O3: 0-4%, and CeO2: 0-2%.
[0013] Calculated by mass percentage of the basic components, the raw materials of the basic components are: Al2O3: 3%~8%, CaO: 13%~18%, MgO: 0.5%~4%, ZnO: 1%~5%, R2O: 1%~6%, BaO: 3%~5%, TiO2: 3%~6%, B2O3: 1%~2%, SnO2: 0.5%~2%, ZrO2: 1.5%~3%, P2O5: 1%~3%, Sb2O3: 0~0.4%, SiO2: make up the balance to 100%.
[0014] Preferably, the R2O is one or more of Li2O, Na2O, and K2O; more preferably, it is Li2O or Na2O.
[0015] Preferably, the mass ratio of Li2O to Na2O is (1-3):1; further preferably, it is 2:1.
[0016] Preferably, the mass ratio of Al2O3 to P2O5 is (2-3):1; further preferably, it is 5:2.
[0017] Preferably, the mass ratio of CaO, BaO, R2O and MgO is (7-8):(1-3):(1-3):1; further preferably, it is 15:4:4:2.
[0018] Preferably, the ratio of the total mass of Al2O3 and P2O5 to the total mass of BaO, CaO, MgO and R2O is 1:(3-4); further preferably, it is 7:25.
[0019] The inventors found that the chemical stability and hardness of colored crystal jade can be improved by selecting a specific ratio of Al2O3, P2O5, BaO, CaO, MgO, and R2O as raw materials. This may be because on the one hand, Al2O3 and P2O5 work together to form a stable network structure, thereby increasing the hardness and density of the glass while enhancing the chemical stability and corrosion resistance of the glass. On the other hand, the BaO, CaO, MgO, and R2O network exosomes can adjust the melting point and viscosity of the glass, not only promoting the melting and forming process of the glass, but also working together with the network formers of Al2O3 and P2O5 to form a more complex network structure, further improving the hardness and chemical stability of the glass. However, in the preparation process, the amount of R2O added should not be too much, as too much will affect the glass phase structure, increase defects, and affect glossiness.
[0020] Preferably, the mass ratio of TiO2, ZrO2, B2O3 and SnO2 is (3-5):(1-3):(1-2):1; further preferably, it is 8:4:3:2.
[0021] The inventors have found that the hardness and glossiness can be improved by selecting a specific ratio of TiO2, ZrO2, B2O3, and SnO2 for compounding. This is because, on the one hand, the synergistic effect of TiO2, ZrO2, and SnO2 can promote the in-situ precipitation of micro-nano crystals in microcrystalline glass, thereby improving its hardness and wear resistance. The oxide components generated by the compounding of ZrO2 and B2O3 can directly improve the hardness of microcrystalline glass, so that the prepared colored crystal jade has high hardness and is not easy to wear. On the other hand, B2O3 and TiO2 can not only reduce the melting temperature of glass and promote the uniform distribution of glass phases, thereby improving the glossiness of microcrystalline glass, but also are glass network formers, which are easy to generate glass phases of various component systems. The existence and increase in the number of these glass phases are conducive to the improvement of the glossiness of microcrystalline glass. The uniform distribution and interaction of these oxides in the glass help to form a glossy and dense glass surface, thereby improving its glossiness.
[0022] Preferably, the mass ratio of ZnO, SnO2 and Sb2O3 is (8-12):(3-4):1; further preferably, it is 30:10:3.
[0023] The inventors found that the selection of a specific ratio of ZnO, SnO2, and Sb2O3 can improve the brightness and chemical stability at the same time. This is because the three work together to adjust the refractive index of the glass on the one hand, making it easier for light to pass through the glass while reducing the scattering and reflection of the glass surface, thereby improving the transmittance of light. On the other hand, it can stabilize the network structure of the glass and reduce the reactivity of the glass surface with chemical substances. In addition, Sb2O3 can remove impurities and bubbles in the glass, thereby reducing impurities and defects in the glass while improving the purity and transparency of the glass, thereby improving the transparency and stability of the glass and increasing the beauty of the jade.
[0024] The specific steps of the melting are: mixing and melting the raw materials, and the heating program is: heating from room temperature to 800-900°C at a heating rate of 3-5°C / min, keeping the temperature for 20-40min, then heating to 1200-1280°C at a heating rate of 4-6°C / min, keeping the temperature for 1.5-2.5h, pouring the melt on a preheated steel plate for molding, and quickly annealing at 530-560°C for 1-3h, and cooling with the furnace to obtain the product.
[0025] The inventors found that melting the raw materials by heating them in steps and then heat treating them can improve the stability and glossiness of jade. This is because step-by-step heating can not only make the glass gradually adapt to the temperature changes during the heating process, reduce the thermal stress caused by the sharp rise in temperature, and avoid the glass from breaking due to excessive stress, but also facilitate the discharge of gas and volatile substances, avoid them from being trapped inside the glass to produce bubbles, and affect the performance and aesthetic effect of jade. The heat treatment process at a specific temperature can further eliminate the residual stress in the glass, improve the thermal shock resistance of the glass, and reduce the defects such as ripples and deformation on the surface of the glass, thereby improving the glossiness and flatness of the glass. In addition, in subsequent processing such as polishing, the heat-treated glass is often easier to achieve the ideal glossiness requirements, which is convenient for processing.
[0026] The specific steps of the secondary melt crystallization are: heating to 830-850°C at a heating rate of 4-8°C / min, and keeping warm for 1-2h; heating to 1050-1110°C at a heating rate of 2-4°C / min, and keeping warm for 20-40min; heating to 1200-1280 at a heating rate of 3-5°C / min, keeping warm for 1-2h, and cooling to room temperature.
[0027] The inventor found that by the secondary melting crystallization process of specific steps, not only can samples of different colors and shapes be mixed to obtain colorful jade, but also the hardness and chemical stability of jade can be improved. This is because the secondary melting crystallization under specific conditions not only makes the crystals in the glass melt continue to grow and interweave at high temperature, forming a more dense and solid microcrystalline glass structure, so that the product has higher strength and hardness, can resist external impact and wear, but also helps to eliminate defects such as bubbles and cracks in the glass, improve the transparency and purity of the product, and optimize the physical properties and chemical stability of the product. In addition, in the secondary melting crystallization process, the glass melts of different colors will further merge and diffuse, making the color of the colorful jade more uniform and full, and the binding force between samples of different colors is high, and it is not easy to fall off and deform. At the same time, the growth and arrangement of crystals will also form a unique texture effect, enhancing the aesthetics and artistic sense of the product. However, the rate, temperature and insulation time of the three heatings need to be strictly controlled, otherwise it will affect the number and size of the crystal nuclei, resulting in difficulty in forming a tight structure between the samples of various colors, not only making each color component also easy to fall off, affecting the overall stability of the product.
[0028] Preferably, the solution of the fixing agent is a ceramic fixing agent aqueous solution.
[0029] Preferably, the mass percentage of the ceramic fixing agent in the ceramic fixing agent aqueous solution is 1% to 2%.
[0030] Preferably, the ceramic fixing agent has a viscosity of 2000-2200 mPa·s at 30° C. and an ash content of ≤0.1%.
[0031] In some preferred embodiments, the ceramic fixative is purchased from Janssen Chemical.
[0032] Preferably, the amount of the ceramic fixing agent used is 200-220 g / m 2 .
[0033] Preferably, the processing includes cutting, edge grinding, polishing and other processes.
[0034] The present invention also includes products prepared by the multi-color stacking synthesis process of the colored crystal jade.
[0035] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0036] 1. The present invention provides a multi-color stacking synthesis process for colored crystal jade, which is simple to operate. The prepared colored crystal jade has high surface gloss, high hardness, and certain chemical stability. At the same time, the raw materials and addition amount of the coloring component are controlled so that the addition of the coloring component does not affect the crystallization of the basic component, thereby making the prepared jade colorful and very suitable for application in the fields of construction, decoration, etc.
[0037] 2. The present invention selects P2O5, Al2O3, BaO, CaO, MgO and R2O in specific proportions as raw materials, which can improve the chemical stability and hardness of colored crystal jade.
[0038] 3. The present invention selects TiO2, ZrO2, SnO2 and B2O3 in a specific ratio to improve hardness and glossiness.
[0039] 4. The present invention selects a specific ratio of ZnO, Sb2O3, and SnO2 to compound, which can improve the brightness and chemical stability at the same time.
[0040] 5. The present invention melts the raw materials by heating them step by step and then performing heat treatment, thereby improving the stability and glossiness of the jade.
[0041] 6. The present invention not only can mix samples of different colors and shapes to obtain colorful jade, but also can improve the hardness and chemical stability of jade through a secondary melting crystallization process with specific steps. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The raw materials used in the present invention are all commercially available, specifically:
[0044] The fixing agent is a ceramic fixing agent with a viscosity of 2000-2200 mPa·s at 30° C. and an ash content of ≤0.1%, purchased from Janssen Chemical.
[0045] Example 1
[0046] This embodiment provides a multi-color stacking synthesis process of colored crystal jade, the steps of which are:
[0047] S1. Weigh the yellow raw material and the green raw material respectively, and melt them to obtain a yellow sample and a green sample respectively;
[0048] S2, stacking the yellow sample and the green sample, and fixing them with a fixative solution to obtain a precursor sample;
[0049] S3, subjecting the precursor sample to secondary melting and crystallization to form a primary sample;
[0050] S4. Process the initial sample to obtain.
[0051] The yellow raw material, by mass percentage, is: 5% yellow component and the balance of basic components to 100%.
[0052] Calculated by weight percentage of the raw materials, the yellow component is Fe2O3: 1%, Mn2O3: 4%.
[0053] The green raw materials, calculated by mass percentage, are: 2% of green components and the balance of basic components to 100%.
[0054] Calculated by weight percentage of the raw materials, the green components are Cr2O3: 0.8% and CuO: 1.2%.
[0055] Calculated by mass percentage of the basic components, the raw materials of the basic components are: Al2O3: 5%, CaO: 15%, MgO: 2%, ZnO: 3%, R2O: 4%, BaO: 4%, TiO2: 4%, B2O3: 1.5%, SnO2: 1%, ZrO2: 2%, P2O5: 2%, Sb2O3: 0.3%, SiO2: add the remainder to 100%.
[0056] The R2O is Li2O or Na2O.
[0057] The mass ratio of Li2O to Na2O is 2:1.
[0058] The specific steps of the melting are: mixing and melting the raw materials, and the heating program is: heating from room temperature to 850°C at a heating rate of 4°C / min, keeping the temperature for 20 to 40 minutes, then heating to 1220°C at a heating rate of 5°C / min, keeping the temperature for 2 hours, pouring the melt onto a preheated steel plate for forming, and quickly annealing at 550°C for 2 hours, and cooling with the furnace to obtain the product.
[0059] The specific steps of the secondary melt crystallization are: heating to 840°C at a heating rate of 6°C / min, keeping warm for 1.5 hours; heating to 1090°C at a heating rate of 3°C / min, keeping warm for 30 minutes; heating to 1220°C at a heating rate of 4°C / min, keeping warm for 1.5 hours, and then cooling to room temperature.
[0060] The solution of the fixing agent is a ceramic fixing agent aqueous solution.
[0061] The mass percentage of the ceramic fixing agent in the ceramic fixing agent aqueous solution is 1.5%.
[0062] The amount of the ceramic fixing agent used is 210 g / m 2 .
[0063] The processing includes cutting, edge grinding and polishing.
[0064] Example 2
[0065] The difference between this embodiment and embodiment 1 is as follows: S1, weighing a gray raw material, a yellow raw material and a green raw material respectively, and melting them to obtain a gray sample, a yellow sample and a green sample respectively;
[0066] S2. Stack the gray sample, the yellow sample and the green sample, and fix them with a fixative solution to obtain a precursor sample.
[0067] The gray raw material, calculated by mass percentage, is as follows: 5% gray component and the balance of basic components to 100%.
[0068] Calculated by weight percentage of the raw materials, the gray components are CoO: 0.1% and NiO: 0.3%.
[0069] Example 3
[0070] The difference between this embodiment and embodiment 1 is that, calculated by mass percentage of the basic components, the raw materials of the basic components are: Al2O3: 6%, CaO: 15%, MgO: 2%, ZnO: 3%, R2O: 3%, BaO: 4%, TiO2: 4%, B2O3: 1.5%, SnO2: 1%, ZrO2: 2%, P2O5: 2%, Sb2O3: 0.3%, SiO2: supplement the remainder to 100%.
[0071] Comparative Example 1
[0072] The difference between this comparative example and Example 1 is that, calculated by mass percentage of the basic components, the raw materials of the basic components are: Al2O3: 5%, CaO: 15%, MgO: 2%, ZnO: 3%, R2O: 8%, BaO: 4%, TiO2: 4%, B2O3: 1.5%, SnO2: 1%, ZrO2: 2%, P2O5: 2%, Sb2O3: 0.3%, SiO2: supplement the balance to 100%.
[0073] Comparative Example 2
[0074] The difference between this comparative example and Example 1 is that, calculated by mass percentage of the basic components, the raw materials of the basic components are: Al2O3: 2%, CaO: 15%, MgO: 2%, ZnO: 3%, R2O: 4%, BaO: 4%, TiO2: 4%, B2O3: 1.5%, SnO2: 1%, ZrO2: 2%, P2O5: 2%, Sb2O3: 0.3%, SiO2: supplement the balance to 100%.
[0075] Comparative Example 3
[0076] The difference between this comparative example and Example 1 is that, calculated by mass percentage of the basic components, the raw materials of the basic components are: Al2O3: 5%, CaO: 15%, MgO: 2%, ZnO: 3%, R2O: 4%, BaO: 4%, TiO2: 4%, B2O3: 0.5%, SnO2: 1%, ZrO2: 2%, P2O5: 2%, Sb2O3: 0.3%, SiO2: supplement the balance to 100%.
[0077] Comparative Example 4
[0078] The difference between this comparative example and Example 1 is that, calculated by mass percentage of the basic components, the raw materials of the basic components are: Al2O3: 5%, CaO: 15%, MgO: 2%, ZnO: 3%, R2O: 4%, BaO: 4%, TiO2: 4%, B2O3: 1.5%, SnO2: 1%, ZrO2: 1%, P2O5: 2%, Sb2O3: 0.3%, SiO2: the remainder is supplemented to 100%.
[0079] Comparative Example 5
[0080] The difference between this comparative example and Example 1 is that, calculated by mass percentage of the basic components, the raw materials of the basic components are: Al2O3: 5%, CaO: 15%, MgO: 2%, ZnO: 3%, R2O: 4%, BaO: 4%, TiO2: 4%, B2O3: 1.5%, SnO2: 1%, ZrO2: 2%, P2O5: 2%, SiO2: supplement the balance to 100%.
[0081] Comparative Example 6
[0082] The difference between this comparative example and Example 1 is that the specific steps of the melting are: the raw materials are mixed and melted, the heating program is: heating to 1310°C at a heating rate of 5°C / min, keeping warm for 2h, pouring the melt onto a preheated steel plate for forming, and quickly annealing at 550°C for 2h, and cooling with the furnace to obtain.
[0083] Comparative Example 7
[0084] The difference between this comparative example and Example 1 is that the specific steps of the melting are: the raw materials are mixed and melted, and the heating program is: heating from room temperature to 850°C at a heating rate of 4°C / min, keeping warm for 20 to 40 minutes, then heating to 1220°C at a heating rate of 5°C / min, keeping warm for 2 hours, pouring the melt onto a preheated steel plate for molding, and cooling to obtain.
[0085] Comparative Example 8
[0086] The difference between this comparative example and Example 1 is that the specific steps of the secondary melt crystallization are: heating to 840°C at a heating rate of 6°C / min, keeping warm for 3h; heating to 1090°C at a heating rate of 3°C / min, keeping warm for 30min; heating to 1220°C at a heating rate of 4°C / min, keeping warm for 1.5h, and then cooling to room temperature.
[0087] Performance Testing
[0088] The gloss, Mohs hardness, and acid and alkali resistance of the prepared colored crystal jade were tested with reference to JCT 872-2000 "Glass-ceramics for architectural decoration". The standard stipulates that the gloss must be ≥85, the Mohs hardness must be ≥5, and after soaking in 1.0% sulfuric acid solution at room temperature for 650 hours and in 10% sodium hydroxide at room temperature for 650 hours, the mass loss rate must be ≤0.2% and the appearance must not change, indicating that the colored crystal jade is of qualified quality. The results are shown in Table 1.
[0089] Table 1 Measurement results
[0090]
[0091]
[0092] According to statistics, the products prepared by the multi-color stacking synthesis process of the colored crystal jade prepared in Examples 1 to 3 of the present invention have high gloss, excellent hardness and acid and alkali resistance. In Example 1, the amount of R2O added is too high, in Example 2, the amount of A12O3 added is too low, in Example 3, the amount of B2O3 added is too low, in Example 4, the amount of ZrO2 added is too low, in Example 5, Sb2O3 is not added, in Example 6, the melting is not carried out in steps, in Example 7, the heat treatment is not carried out, and in Example 8, the first stage of the secondary melting crystallization is too long. The hardness, gloss, and acid and alkali resistance of the prepared products do not fully meet the requirements. Therefore, the multi-color stacking synthesis process of the colored crystal jade described in this application is simple to operate, and the prepared colored crystal jade is rich in color, has high surface gloss, high hardness, and has certain chemical stability.
[0093] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A multi-color stacking synthesis process of colored crystal jade, characterized in that: The following steps are involved: S1. Weigh the raw materials according to the required color system, mix and melt them into samples of different colors and shapes; S2, stacking samples of different colors and shapes according to the required colors and shapes, and fixing them with a fixative solution to obtain a precursor sample; S3, subjecting the precursor sample to secondary melting and crystallization to form a primary sample; S4, processing the initial sample to obtain; The raw materials, by mass percentage, are composed of: 0.01% to 7% of coloring components and the balance of basic components to 100%; According to the weight percentage of the raw materials, the coloring components are Fe2O3: 0-1.5%, Mn2O3: 0-5%, Cr2O3: 0-4%, CuO: 0-4%, Cu2O: 0-4%, CoO: 0-2%, Co2O3: 0-5%, NiO: 0-0.5%, Er2O3: 0-0.5%, Bi2O3: 0-4%, CeO2: 0-2%; According to the mass percentage of the basic components, the raw materials of the basic components are: Al2O3: 3% to 8%, CaO: 13% to 18%, MgO: 0.5% to 4%, ZnO: 1% to 5%, R2O: 1% to 6%, BaO: 3% to 5%, TiO2: 3% to 6%, B2O3: 1% to 2%, SnO2: 0.5% to 2%, ZrO2: 1.5% to 3%, P2O5: 1% to 3%, Sb2O3: 0 to 0.4%, SiO2: the balance is supplemented to 100%; The specific steps of the melting are: mixing and melting the raw materials, and the heating program is: heating from room temperature to 800-900°C at a heating rate of 3-5°C / min, keeping the temperature for 20-40min, then heating to 1200-1280°C at a heating rate of 4-6°C / min, keeping the temperature for 1.5-2.5h, pouring the melt on a preheated steel plate for forming, and quickly annealing at 530-560°C for 1-3h, and cooling with the furnace to obtain; The specific steps of the secondary melt crystallization are: heating to 830-850°C at a heating rate of 4-8°C / min, and keeping warm for 1-2h; heating to 1050-1110°C at a heating rate of 2-4°C / min, and keeping warm for 20-40min; heating to 1200-1280°C at a heating rate of 3-5°C / min, and keeping warm for 1-2h, and then cooling to room temperature; The mass ratio of Al2O3 and P2O5 is (2-3):1; The mass ratio of CaO, BaO, R2O, and MgO is (7-8): (1-3): (1-3): 1; The ratio of the total mass of Al2O3 and P2O5 to the total mass of BaO, CaO, MgO and R2O is 1:(3-4); The mass ratio of TiO2, ZrO2, B2O3, and SnO2 is (3-5): (1-3): (1-2): 1; The mass ratio of ZnO, SnO2 and Sb2O3 is (8~12):(3~4):
1.
2. The multi-color stacking synthesis process of colored crystal jade according to claim 1, characterized in that: The R2O is one or more of Li2O, Na2O, and K2O.
Citation Information
Patent Citations
Making crystal glass like natural stone by sintering-fractional crystallizing technique
CN1035650A
Crystallized glass article having patterns and method of producing the same
US20070048529A1